2017
DOI: 10.1007/s12035-017-0730-0
|View full text |Cite
|
Sign up to set email alerts
|

Early Exposure to Ketamine Impairs Axonal Pruning in Developing Mouse Hippocampus

Abstract: Mounting evidence suggests that prolonged exposure to general anesthesia (GA) during brain synaptogenesis damages the immature neurons and results in long-term neurocognitive impairments. Importantly, synaptogenesis relies on timely axon pruning to select axons that participate in active neural circuit formation. This process is in part dependent on proper homeostasis of neurotrophic factors, in particular brain-derived neurotrophic factor (BDNF). We set out to examine how GA may modulate axon maintenance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…111,112 Further investigation is needed to better understand why other anaesthetics, such as ketamine, affect the infrapyramidal bundle differently than propofol; for example, ketamine exposure of neonatal rodents results in decreased infrapyramidal pruning. 113 Propofol acts primarily through gaminobutyric acid agonism, while ketamine acts through Nmethyl-D-aspartate receptor antagonism. There is evidence for a complex interplay between dimethylnitrosamine receptor activity and Rho GTPase activation.…”
Section: Discussionmentioning
confidence: 99%
“…111,112 Further investigation is needed to better understand why other anaesthetics, such as ketamine, affect the infrapyramidal bundle differently than propofol; for example, ketamine exposure of neonatal rodents results in decreased infrapyramidal pruning. 113 Propofol acts primarily through gaminobutyric acid agonism, while ketamine acts through Nmethyl-D-aspartate receptor antagonism. There is evidence for a complex interplay between dimethylnitrosamine receptor activity and Rho GTPase activation.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that one type of acute damage to the developing brain induced by AASDs is increased apoptotic neurodegeneration, which likely involves N-methyl-D-aspartate (NMDA) glutamate receptor antagonism or potentiation of γ-aminobutyric acid A (GABA A ) receptors 12 . Recent animal studies have shown AASDs also impair neuronal function by disturbing timely axonal pruning and cues that promote accurate directional growth of axons during development 13,14 . Preclinical research has been valuable in defining the spatial and temporal patterns of the acute apoptotic damage, which is widespread and includes cell-type-specific patterns 1–3 .…”
Section: Introductionmentioning
confidence: 99%
“…This study was prompted by the finding that in addition to neuron death, exposure to anesthetic agents in the neonatal period results in disrupted synapse architecture, mitochondrial morphology and axonal pruning [37][38][39]. We attempted to delineate the contribution of neuron death from other potentially injurious effects associated with exposure to volatile anesthetics in the neonatal period using Bax knockout mice.…”
Section: Discussionmentioning
confidence: 99%